2020
DOI: 10.3390/coatings10080742
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Substrate Rotation Speed on Structure and Adhesion Properties of CrN/CrAlSiN Multilayer Coatings Prepared Using High-Power Impulse Magnetron Sputtering

Abstract: We investigated the effects of substrate rotation speed on the structural and mechanical properties of CrN/CrAlSiN multilayer coatings produced using high-power impulse magnetron sputtering (HiPIMS) on silicon and high-speed steel (HSS) substrates. Structural analysis and characterization of the multilayer coatings were performed using an X-ray diffractometer (XRD), field emission scanning electron microscopy (FE-SEM), an electron probe microanalyzer (EPMA), and a transmission electron microscope (TEM). The th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
(58 reference statements)
1
4
0
Order By: Relevance
“…Specifically, reducing the substrate rotation speed leads to an increase in the thickness and roughness of the sputtered films on both substrates. This observation aligns with the findings [ 27 ] that reported a correlation between substrate rotation speed and film thickness. The study was noted that a lower speed of 1.5 rpm resulted in a film thickness of 12 nm, whereas a higher speed of 5 rpm led to a reduced thickness of only 3.2 nm.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, reducing the substrate rotation speed leads to an increase in the thickness and roughness of the sputtered films on both substrates. This observation aligns with the findings [ 27 ] that reported a correlation between substrate rotation speed and film thickness. The study was noted that a lower speed of 1.5 rpm resulted in a film thickness of 12 nm, whereas a higher speed of 5 rpm led to a reduced thickness of only 3.2 nm.…”
Section: Discussionsupporting
confidence: 93%
“…SRS also impacts grain size. , Sputtered atoms adsorbed on the surface of deposited thin films diffuse, forming larger grains by gathering and merging . Higher substrate rotation speeds impede this phenomenon by reducing the adatom energy, resulting in smaller grains due to lower diffusion strength.…”
Section: Resultsmentioning
confidence: 99%
“…Substrate rotation speed in the sputtering process is revealed to affect film hardness, adhesion strength, and residual stress . Higher rotation speeds enhance hardness and adhesion while reducing residual stress by minimizing collisions of sputtered high-energy ions with films. , Recent studies demonstrated significant improvements in nanostructured Ni anode connectivity and GDC interlayer films in SOFC by adjusting rotation speed and target-substrate configuration. , …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, more than one element was added, e.g., Y and O [138]. Multilayer architectures were built using CrAlSiN and AlCrSiN combined, for example, with Si-free AlCrN layers [139], with AlSiN [140], or with coatings containing Si, such as Cr-doped AlSiN [127], with MoN, NbN [139], or with CrN [141], and others.…”
Section: Coatings With the Addition Of Simentioning
confidence: 99%